2019
DOI: 10.1139/anc-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Capture, ingestion, and egestion of microplastics by suspension-feeding bivalves: a 40-year history

Abstract: In aquatic environments, suspension-feeding bivalve molluscs are exposed to a manifold of natural and anthropogenically derived particles, including micro- and nanoplastics. Plastic particles interact with feeding and digestive organs and can produce negative effects. As a result of these effects and the potential transfer of microplastics to higher trophic levels, including humans, there has been renewed interest in the ingestion of plastic particles by different species of bivalves. Many recent studies, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 66 publications
(87 reference statements)
0
87
0
Order By: Relevance
“…Bivalve molluscs have been widely used for coastal monitoring anthropogenic aquatic contaminants such as heavy metals (Goldberg et al, 1978;Azizi et al, 2018), micro plastics (Ward, Rosa & Shumway, 2019) and human pathogen transmission (Gyawali et al, 2019;Razafimahefa, Ludwig-Begall & Thiry, 2019) together with seasonal ecotoxicological problems such as algal blooms (Gibble, Peacock & Kudela, 2016;Hinder et al, 2011). Their shells have also been used for almost four decades as a proxy to determine exposure to heavy metal concentrations in modern samples (Yap et al, 2002;Koide, Lee & Goldberg, 1982), historic (Wing et al, 2019) and archaeological samples (Binkowski et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bivalve molluscs have been widely used for coastal monitoring anthropogenic aquatic contaminants such as heavy metals (Goldberg et al, 1978;Azizi et al, 2018), micro plastics (Ward, Rosa & Shumway, 2019) and human pathogen transmission (Gyawali et al, 2019;Razafimahefa, Ludwig-Begall & Thiry, 2019) together with seasonal ecotoxicological problems such as algal blooms (Gibble, Peacock & Kudela, 2016;Hinder et al, 2011). Their shells have also been used for almost four decades as a proxy to determine exposure to heavy metal concentrations in modern samples (Yap et al, 2002;Koide, Lee & Goldberg, 1982), historic (Wing et al, 2019) and archaeological samples (Binkowski et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The blue mussel (Mytilus edulis) and Mediterranean mussel (Mytilus galloprovincialis) have been widely used in assessing the risks posed by environmental stressors (Farrington et al, 2016;Viarengo and Canesi, 1991). Mussels are omnivorous suspension feeders with proven capacity for consuming microplastics (Ward et al, 2019a). Numerous field-studies have demonstrated that mussels can readily consume microplastic debris under environmental conditions (De Witte et al, 2014;Li et al, 2018;Li et al, 2015;Rochman et al, 2015;Santana et al, 2016;Van Cauwenberghe and Janssen, 2014;Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Top is a summary of two-way ANOVA of the effect of abiotic particle type and concentration on mussel CR. Microplastics may reduce CR at high concentrations as a result of unique surface properties that affect the filtration process (Ward and Shumway 2004;Rosa et al 2017;Ward et al 2019). Abiotic proportion is the concentration of abiotic particles (MP or silt) divided by the total particle concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller MP and silt are similar in many characteristics, including size, and lack of nutritional value. Capturing and processing nutrient poor particles can reduce a mussel's energy budget by increasing feeding costs (sorting abiotic particles) or inducing a false sense of fullness, ultimately leading to less energy allocated to maintenance and growth (Widdows and Johnson 1988;Ward et al 2019). Silt has been shown to both positively and negatively affect mussel clearance and growth, creating uncertainty in how mussel CR will respond to similar abiotic particles, like MP (e.g., Bayne et al 1987;Denis et al 1999;Ward and Shumway 2004).…”
mentioning
confidence: 99%